2014
DOI: 10.1111/bph.12491
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids suppress hypoxia‐induced COX‐2 and hypoxia inducible factor‐1α expression through the induction of glucocorticoid‐induced leucine zipper

Abstract: BACKGROUND AND PURPOSEThe COX-2/PGE2 pathway in hypoxic cancer cells has important implications for stimulation of inflammation and tumourigenesis. However, the mechanism by which glucocorticoid receptors (GRs) inhibit COX-2 during hypoxia has not been elucidated. Hence, we explored the mechanisms underlying glucocorticoid-mediated inhibition of hypoxia-induced COX-2 in human distal lung epithelial A549 cells. EXPERIMENTAL APPROACHThe expressions of COX-2 and glucocorticoid-induced leucine zipper (GILZ) in A54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 38 publications
3
36
1
2
Order By: Relevance
“…HIF1A belongs to the hypoxia-inducible factor family that plays a critical role in hypoxic stress (44,45). SUMOylation can also modulate the HIF1A action during hypoxia (46,47), and glucocorticoids are capable of suppressing HIF1A expression through the induction of glucocorticoid-induced leucine zipper (48).…”
Section: Discussionmentioning
confidence: 99%
“…HIF1A belongs to the hypoxia-inducible factor family that plays a critical role in hypoxic stress (44,45). SUMOylation can also modulate the HIF1A action during hypoxia (46,47), and glucocorticoids are capable of suppressing HIF1A expression through the induction of glucocorticoid-induced leucine zipper (48).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin F2α (PGF2α), like oxytocin, is a major stimulator of uterine activity in labor (22). Hypoxia has been shown to up-regulate COX2 and increase prostaglandin production in smooth muscle and other tissues (23,24), and this has been hypothesized to contribute to labor (25). We therefore investigated the effects of inhibiting prostaglandin biosynthesis on HIFI by blocking the cyclo-oxygenases.…”
Section: Cox2 and Intracellular Camentioning
confidence: 99%
“…Glucocorticoid strongly suppresses COX-2 expression induced by inflammatory stimuli (Lim et al 2014;Yang et al 2008). To assess the involvement of the well-known anti-inflammatory glucocorticoid receptor (GR) pathway in the KRG-WE inhibition of hypoxia induced COX-2 in A549 cells, we pre-incubated cells with the GR antagonist RU486 for 1 h and co-treated with hypoxia.…”
Section: The Effects Of Krg-we On Gr Pathwaymentioning
confidence: 99%
“…Recently, we reported glucocorticoid-induced leucine zipper (GILZ) plays a major role in suppression of hypoxia-induced COX-2 (Lim et al 2014). It suggested that GILZ is an important molecular therapeutic target for the inflammatory response and tumorigenesis in lung cancer.…”
Section: The Effects Of Krg-we On Gr Pathwaymentioning
confidence: 99%